Rancang Bangun Sistem Monitoring Volume Bahan Bakar Minyak di Atas Kapal Berbasis ESP32 - Muhammad Bima Saktia Kharissena; Agus Dwi Santoso; Dyah Ratnaningsih (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
From this research, monitoring can be done using an ESP32 microcontroller that can run the HY-SRF05 ultrasonic sensor to take measurements of fuel in the tank and then the measurement results can be seen on the connected android. This tool is made to monitor the volume of fuel oil on board via android without having to check to the field. From the results of this study, it is obtained that the HY-SRF05 ultrasonic sensor can measure the fuel level (cm) with a distance of 30 cm from the bottom depth of the tank and then the fuel level data (cm) is processed by ESP32 and then the height data from the sensor reading is displayed via android which has been connected online via an internet connection in the form of fuel volume (L). Tests were carried out 10 (ten) times with 3 (three) different capacities, namely with a capacity of 25%, 50%, and 75% of the maximum capacity of the fuel and with 2 (two) test methods, namely testing in stationary tank conditions (A) and testing in tank conditions getting shocks (B). So that from this test, the total value of the tool error (error) in the stationary tank condition (A) is 0.426% and in the condition of the tank getting a shock (B) of 0.420%. Based on the test results, the tool is said to be able to work well between measurements using the HY-SRF05 ultrasonic sensor and the actual depth with a system accuracy level of 99.57%.